Multilayer Epitaxial Heterostructures with Multi-Component III–V:Fe Magnetic Semiconductors - Alexey V. Kudrin; Valeri P. Lesnikov; Ruslan N. Kriukov; Yuri A. Danilov; Mikhail V. Dorokhin; Anastasia A. Yakovleva; Nataliya Yu. Tabachkova; Nikolai A. Sobolev (Nanomaterials, 2023)
Three-layer structures based on various multi-component films of III–V semiconductors heavily doped with Fe were grown using the pulsed laser sputtering of InSb, GaSb, InAs, GaAs and Fe solid targets. The structures comprising these InAsSb:Fe, InGaSb:Fe and InSb:Fe layers with Fe concentrations up to 24 at. % and separated by GaAs spacers were deposited on (001) i-GaAs substrates at 200 °C. Transmission electron microscopy showed that the structures have a rather high crystalline quality and do not contain secondary-phase inclusions. X-ray photoelectron spectroscopy investigations revealed a significant diffusion of Ga atoms from the GaAs regions into the InAsSb:Fe layers, which has led to the formation of an InGaAsSb:Fe compound with a Ga content up to 20 at. %. It has been found that the ferromagnetic properties of the InAsSb:Fe magnetic semiconductor improve with an increasing Sb:As ratio. It has been concluded that the indirect ferromagnetic exchange interaction between Fe atoms occurs predominantly via Sb atoms.